Injuries among Portuguese skiers and snowboarders - Martins, A.; Silva, B.; Camões, M.; Pereira, J.; Clemente, FM. (SPORT TK-EuroAmerican Journal of Sport Sciences, 2020)
With the introduction of Snowboarding into the world there has been a huge increase in the number of winter sports enthusiasts. This study’s aim is to analyse and compare the injury profiles associated to Portuguese Skiers and Snowboarders. A total of 218 individuals completed a 2 years retrospective questionnaire, of which 87 (40%) of them were Skiers, 113 (52%) Snowboarders and 18 (8%) practised both sports. A total of 107 (49%) subjects were injured, with 42 (39.3%) Ski related and 72 (67.3%) Snowboard related injuries. The most frequent body location of injury was the knee in both sports (59.5% in Ski and 31.9% in Snowboard). In conclusion we observe that Snowboarding has a higher risk of injury compared to Skiing.